2013
DOI: 10.1515/bmt-2013-4083
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an in vitro evaluation system for drug-coated ballons

Abstract: Translation of the Bible or any other text unavoidably involves a determination about its meaning. There have been different views of meaning from ancient times up to the present, and a particularly Enlightenment and Modernist view is that the meaning of a text amounts to whatever the original author of the text intended it to be. This article analyzes the authorial-intent view of meaning in comparison with other models of literary and legal interpretation. Texts are anchors to interpretation but are subject t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this study, although drug concentrations in the arterial tissues decreased with time, they were still detectable up to 2 weeks after delivery, leading to the reduction of neointimal proliferation efficiently. The past decade has witnessed extensive use of commercially available hydrogelcoated balloons to locally deliver drugs like paclitaxel 13 , heparin 46 , and argatroban 47 , among others. In our study, we observed that the hydrogel coatings showed significantly enhanced NP loading and more efficient NP transfer to the arterial wall compared to those of LbL and dip coatings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, although drug concentrations in the arterial tissues decreased with time, they were still detectable up to 2 weeks after delivery, leading to the reduction of neointimal proliferation efficiently. The past decade has witnessed extensive use of commercially available hydrogelcoated balloons to locally deliver drugs like paclitaxel 13 , heparin 46 , and argatroban 47 , among others. In our study, we observed that the hydrogel coatings showed significantly enhanced NP loading and more efficient NP transfer to the arterial wall compared to those of LbL and dip coatings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that it is challenging to produce a uniform and thin layer of hydrogel coating on the balloon, and our study also observed the non-uniform hydrogel coating. Kaule et al 13 highlighted the influence of the balloon coating structure (namely coating thickness) or the coating material on the performance of angioplasty balloons. This study observed reduced paclitaxel (PTX) loss, and superior PTX transfer in the case of balloons where the PTX was incorporated into a coating matrix of excipients such as cetylpyridinium salicylate (cetpyrsal) (18.94 μm thick) compared to hyaluronic acid (HA) (32.98 μm thick) and Polyvinylpyrrolidone (PVP) (34.11 μm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation